SCHOOL - PLACE OF ELITISM AND HUMANISM IN SPORT - Zoran Milošević; Nebojša Maksimović; Borislav Obradović; Nada Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
School sport is defined both by legal solutions giving form to the educational process of primary and secondary schools and by those dealing with sport issues directly. Importance of school is indicated by the fact that it is the place where sport is realized within a mass-like and humanist framework with non-commercial base. In view of high decade-long investments of institutions of the Republic and Province, especially the City of Novi Sad, into outdoor and indoor facilities for practicing physical education (sport), as well as high professional and educational level of the personnel directly involved in this process, one can rightly ask a question: IS SCHOOL A PLACE OFFERING EQUAL OPPORTUNITIES FOR SPORTS ACHIEVEMENTS TO CHILDREN AND YOUTH?